Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s40201-017-0274-2
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic use of plant and isolated bacteria to clean up polycyclic aromatic hydrocarbons from contaminated soil

Abstract: BackgroundBiological methods of polycyclic aromatic hydrocarbons (PAH) contamination elimination typically involve the transformation of contaminants to non-toxic materials by microorganisms and plants and appear to be the most effective methods available.MethodsIn this study, Bacillus licheniformis and Bacillus mojavensis isolated from oil-contaminated soils were inoculated onto Festuca arundinacea seeds before planting in the pot and 3 weeks after planting by syringe injection into the rhizospheric zone in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Rhizoremediation is one specific subset of phytoremediation, in which plant-associated rhizosphere microorganisms are used for treatment of polluted soils (Das and Das, 2015). Rhizoremediation is more intensive for PAH degradation and a key of successful rhizoremediation is dependent on the appropriate partnership of plant and microbes that have degradation capabilities (Agnello et al, 2016;Eskandary et al, 2017). Plants provide the huge root surface area for microbial growth and remediate pollutants approximately 10-15 m deep in the soil (Bisht et al, 2015).…”
Section: Strategies For Polycyclic Aromatic Hydrocarbon Bioremediationmentioning
confidence: 99%
“…Rhizoremediation is one specific subset of phytoremediation, in which plant-associated rhizosphere microorganisms are used for treatment of polluted soils (Das and Das, 2015). Rhizoremediation is more intensive for PAH degradation and a key of successful rhizoremediation is dependent on the appropriate partnership of plant and microbes that have degradation capabilities (Agnello et al, 2016;Eskandary et al, 2017). Plants provide the huge root surface area for microbial growth and remediate pollutants approximately 10-15 m deep in the soil (Bisht et al, 2015).…”
Section: Strategies For Polycyclic Aromatic Hydrocarbon Bioremediationmentioning
confidence: 99%
“…have been documented(Ramezani, Rahmani & Dehestani, 2017;Naz et al, 2017). Few plants extraction and effective bacteriostatic component exhibited synergistic or additive interaction with antibiotics against drug-resistant bacteria(Eskandary, Tahmourespour, Hoodaji & Abdollahi, 2017; Ye et al, 2017). Screening of crude extracts for synergistic or additive interaction with antibiotics is expected to provide bioactive compounds to be used in combinational therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the study of Pinsker [14][15][16], which reported that initial soil PCB has a great effect on the amount of PCB absorbed by plants, its translocation as well as the concentrations of the residual PCB in the soil at the end of a phytoremediation study. There was higher mean percentage reduction of PCB concentration in the entire experiment compared to the mean percentage PCB reductions of other plants species in phytoremediation studies reported in literature per unit time [15][16][17][18][19][20][21][22]. However PCB reduction was also observed at the unplanted control, the reason behind such observation could be attributed to natural attenuation and perhaps other parameters not measured.…”
Section: Growth Of C Odorata In Transformer Oil Contaminated Soilmentioning
confidence: 79%
“…Phytoremediation is cost effective and eco-friendly strategy that can complement or replace conventional approaches especially in the remediation of soil contaminated by PCBs. The principle mechanism of phytoremediation is either by stimulation of soil microbial activity and degradation of contaminants or through plant uptake of contaminants or by even their degradation products [11][12][18][19] Chlomolaena odorata (L) R.M. King & H. Robinson (Siam weed) is an invasive bushy shrub of South American origin.…”
Section: Introductionmentioning
confidence: 99%